THE INFLUENCE OF EMPLOYEE ENGAGEMENT, WORK LIFE BALANCE AND EMPLOYEE BURNOUT ON THE WORK PERCEPTIONS OF MILLENNIALS IN SURAKARTA - Djafar Maulana; Ahmad Mardalis (Universitas Maarif Hasyim Latif, 2023)
The purpose of this study was to analyse the effect of Employee Engagement, Work Life Balance and Employee Burnout on the work perceptions of the millennial generation in Surakarta. The type of research used in the study uses quantitative methods. The population in this study were all young millennials who are working in the city of Surakarta. This sampling uses a non-probability sampling design with a saturated sample type for data collection. The sample size for this study was 180 respondents. This research uses primary data in its preparation. The data collection method used in this research is by distributing questionnaires. The data analysis technique uses SMARTPLS software. The results showed that Employee Engagement has an effect on the work perceptions of the millennial generation, which is proven to be true. Work life balance affects the work perceptions of the millennial generation, it is proven to be true. Burnout affects the work perceptions of the millennial generation, it is proven to be true.